GAMBARAN PENYEBAB KEJADIAN RUPTUR PERINEUM PADA IBU BERSALIN DI PMB MASSIANA KABUPATEN SINTANG - Haryanti, Yunida; Masan, Lea; Amartani, Rizki; Montessori, Yolanda; Kurniati, Paskalia Tri; Efifania Ose Payon, Hearty (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2025)
Background: WHO reports the morbidity rates of pregnant and giving birth include obstetric complications (3.6%), toxemia gravidarum (5.8%), obstetric trauma including birth canal lacerations and hematomas (5.0%) and perineal lacerations (1 .7%) and other trauma (3.9%). Objective: To find out the description of the factors that cause perineal rupture in pregnant women. Research Methods: This sampling technique researchers used a total sampling technique. The research instrument uses a checklist sheet. Data analysis used Univariate analysis. Results: 43 respondents (40%) had perineal rupture with primiparous parity, part of the perineal rupture occurred at <2 years birth spacing, some of the mothers were 44 respondents (41%), perineal rupture occurred due to parturition persipitatus, part of the 44 respondents (41%) gave birth to mothers, 45 respondents (42%) had perineal rupture due to prolonged labor, and 8 respondents (7%) had birth weight > 4000 grams. Suggestion: To be able to work with mothers in the delivery process by paying more attention to risk factors that can affect the incidence of perineal rupture.